Learn from Home with a Simple Think Pair Share - Widhiasih, Luh Ketut Sri (Institut Hindu Dharma Negeri Denpasar, 2021)
When learn from home becomes a new normal, teachers should switch the class to online. Meanwhile, mastering writing skill is still important in online class because the subjects will be able to express their ideas, feeling and experiences in the written form appropriately. The objective of this study was to find out whether or not writing skill of second semester students of English Language Education Study Program, Faculty of Teacher Training, Mahasaraswati Denpasar University in Academic year 2019/2020 could be improved trough Think Pair Share with distance learning model. The study was designed in the form of classroom action research. Based on the result of the pre-test, post-test, and questionnaire, it could be concluded that writing skill of the second semester students of English Language Education Study Program, Faculty of Teacher Training, Mahasaraswati Denpasar University in Academic Year 2019/2020 could be improved trough Think Pair Share with distance learning model.